Notas acerca de la colección de Orchidaceae del Herbario del Instituto Superior Pedagógico de Pinar del Río (HPPR), Cuba - Mújica Benítez, Ernesto (Lankesteriana: International Journal on Orchidology, 2016)
A revision and a checklist of the Orchidaceae specimens kept at the Herbario of the Facultad de Biología, Instituto Superior Pedagógico de Pinar del Río, Cuba, are presented. The orchid collection of this herbarium is almost unknown to the students of the orchid flora of Cuba, and it hosts the better and larger collection of specimens from the province of Pinar del Río, from which a third part of all orchid taxa from Cuba are recorded.